1997
DOI: 10.1080/135048697334809
|View full text |Cite
|
Sign up to set email alerts
|

Fast numerical valuation of American, exotic and complex options

Abstract: The purpose of this paper is to present evidence in support of the hypothesis that fast, accurate and parametrically robust numerical valuation of a wide range of derivative securities can be achieved by use of direct numerical methods in the solution of the associated PDE problems. Specifically, linear programming methods for American vanilla and exotic options, and explicit methods for a three stochastic state variable problem (a multi-period terminable differential swap) are explored and promising numerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Note that implicit finite difference methods have occasionally been used for multidimensional problems in finance (Brennan and Schwartz, 1980;Wilmott et al, 1993;Dempster and Hutton, 1997), but it has recently been demonstrated in that the FVM has several advantages over finite difference schemes in this context.…”
mentioning
confidence: 99%
“…Note that implicit finite difference methods have occasionally been used for multidimensional problems in finance (Brennan and Schwartz, 1980;Wilmott et al, 1993;Dempster and Hutton, 1997), but it has recently been demonstrated in that the FVM has several advantages over finite difference schemes in this context.…”
mentioning
confidence: 99%
“…After that convergence becomes fast linear. Discretized nonlinear complementarity problems generated from the upstream weighting with the Van Leer nonlinear flux limiter have additional degeneracy: the Jacobian of the constraintsḠ(x, y) = 0 can be singular when V down = V up , as can be seen from the definition of G given in (10). We observe that, though the proposed method takes slightly more iterations when G(x, y) is nonlinear, convergence is still rapid.…”
Section: G(x Y)mentioning
confidence: 77%
“…In addition, linear complementarity problems with non-tridiagonal coefficient matrices can arise in different asset pricing models, e.g., a jump diffusion model [21]. Computational investigation of American option pricing using the discretized linear complementarity has been made in [11,10,12,15]. In [20], the projected SOR approach has been considered.…”
mentioning
confidence: 99%
“…The application of our method to gammas (second-order sensitivities to interest rate shocks) are given in Sec. 11. In Sec.…”
Section: Introductionmentioning
confidence: 99%